2015
DOI: 10.1101/029249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of increased larval competitive ability inDrosophila melanogasterwithout increased larval feeding rate

Abstract: Multiple experimental evolution studies on D. melanogaster in the 1980s and 1990s indicated that enhanced competitive ability evolved primarily through increased larval tolerance to nitrogenous wastes and increased larval feeding and foraging rate, at the cost of efficiency of food conversion to biomass, and this became the widely accepted view of how adaptation to larval crowding evolves in fruitflies. We recently showed that populations of D. ananassae and D. n. nasuta subjected to extreme larval crowding ev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(39 citation statements)
references
References 45 publications
3
36
0
Order By: Relevance
“…Archana (2010) had found that the suit of larval traits that has evolved in our study populations is very different from the suit of larval traits that had evolved in the r and K populations (Mueller, 1988) or the CU and UU populations . Taken together, the results of Archana (2010), Sarangi et al (2015) and our study show that adaptation to larval crowding can occur through more than one set of mechanisms. Such alternative mechanisms of adaptation to crowding have been detected by multiple other studies (Joshi & Thompson, 1995;Joshi et al, 2001;Dey et al, 2012;Nagarajan et al, 2014).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Archana (2010) had found that the suit of larval traits that has evolved in our study populations is very different from the suit of larval traits that had evolved in the r and K populations (Mueller, 1988) or the CU and UU populations . Taken together, the results of Archana (2010), Sarangi et al (2015) and our study show that adaptation to larval crowding can occur through more than one set of mechanisms. Such alternative mechanisms of adaptation to crowding have been detected by multiple other studies (Joshi & Thompson, 1995;Joshi et al, 2001;Dey et al, 2012;Nagarajan et al, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…However, consistent with the results of the previous studies, the selected larvae had increased competitive ability and larval survivorship under crowded conditions. Thus, the mechanisms that underlie adaptations to larval crowding in the populations of Archana (2010) and Sarangi et al (2015) are very different from those found in the populations of Mueller et al (1993). Therefore, as suggested by other studies (Joshi & Thompson, 1995;Joshi et al, 2001;Dey et al, 2012;Nagarajan et al, 2014), there are multiple ways of adapting to larval crowding.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Due to the limited mobility of larvae [28,29], behavioural avoidance cannot prevent larval exposure to environmental toxins accumulating in the food, but physiological mechanisms help larvae to cope with toxic compounds [30,31]. Drosophila melanogaster populations reared under crowded larval conditions exhibit greater competitive ability [22,32] and increased resistance to both urea and ammonia [22,33]. While the response of D. melanogaster to high levels of urea and ammonia has already been studied [22,33], little is known about the effects in D. suzukii.…”
Section: Introductionmentioning
confidence: 99%